NONTUBERCULOUS MYCOBACTERIA - CURRENT RISK IN BULGARIA - Yuliana Atanasova; Stanislava Yordanova; Ana Baykova; Elizabeta Bachiyska (Problems of Infectious and Parasitic Diseases, 2024)
Background: Nontuberculous mycobacteria (NTM) are generally free-living and have a potential to cause opportunistic infection. More than 190 species of NTM have been identified (http://www.bacterio.net/mycobacterium.html), up to 60 species of them are pathogenic. The distribution is geographically specific for some species and others are cosmopolitan. Understanding their diversity has practical value for the treatment and management of NTM disease. Except for isolated reports, there is no accurate information about NTM spread among Bulgarian patients.